2009
DOI: 10.1111/j.1467-6427.2009.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic factors in a systemic multi‐family group treatment for major depression: patients' and partners' perspectives

Abstract: This study investigated helpful and disturbing factors in multi-family groups with hospitalized, depressed patients and their family members. Both patients and their partners reported the occurrence of different therapeutic factors such as the cohesion of the group, different observational processes, and guidance from the therapist. The frequency of the therapeutic factors seemed to increase for both the patients and their partners as the group sessions progressed and several differences in reported therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
4
18
0
2
Order By: Relevance
“…Secondly, therapeutic alliance seems to be at the core of MFT group dynamics. As indicated by Lemmens, Eisler, Dierick, Lietaer, and Demyttenaere (), Lemmens et al. (), and Hellemans et al.…”
Section: Discussionmentioning
confidence: 76%
“…Secondly, therapeutic alliance seems to be at the core of MFT group dynamics. As indicated by Lemmens, Eisler, Dierick, Lietaer, and Demyttenaere (), Lemmens et al. (), and Hellemans et al.…”
Section: Discussionmentioning
confidence: 76%
“…This has prompted the development of an alternative and more intensive form of family intervention, multi-family therapy (MFT) in which several families are seen together to maximize family resources, encourage cooperation and support between families and help resolve the stuck therapeutic situations that sometimes develop in any treatment context (Asen and Scholz, 2010;Eisler et al, 2010). MFT, originally pioneered by Laqueur et al (1964) has been applied in a variety of conditions, including schizophrenia (Anderson, 1983;McFarlane, 1993), substance misuse (Kaufman and Kaufman, 1979), depression (Lemmens et al 2009a(Lemmens et al , 2009b, chronic medical illness (Steinglass, 1998), child abuse (Asen et al, 1989) and eating disorders (Eisler, might otherwise require inpatient or day care. It draws on the theoretical concepts of the family therapy approach developed at the Maudsley Hospital (Dare et al, 1990;Eisler, 2005;Eisler et al, 2010;Lock and Le Grange, 2013) that places a strong emphasis on mobilizing family resources as a way of overcoming the eating disorder in the young person, and integrates it with the intensive form of MFT developed by Asen and colleagues (Cooklin et al, 1983;Asen and Scholz, 2010).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…() has been applied in a variety of conditions, including schizophrenia (Anderson, ; McFarlane, ), substance misuse (Kaufman and Kaufman, ), depression (Lemmens et al . ), chronic medical illness (Steinglass, ), child abuse (Asen et al ., ) and eating disorders (Eisler, ; Scholz and Asen, ; Scholz et al ., ; Slagerman and Yager, ; Wooley and Lewis, ). Asen and Scholz () provide a detailed review of MFT and also describe the general theoretical concepts and techniques and variety of formats and settings in which it can be used.…”
mentioning
confidence: 99%
“…Studies by Leff et al (2000) and Lemmens et al (2009) show that Systemic Couple Therapy is more effective than medication at 2-year follow up. Lemmens et al utilized a mix of multi-family groups, couple sessions, and family sessions and found that the outcomes were much better than medication alone.…”
Section: Depression and Anxietymentioning
confidence: 98%